2018
DOI: 10.1016/j.aninu.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Dietary modulation of endogenous host defense peptide synthesis as an alternative approach to in-feed antibiotics

Abstract: Traditionally, antibiotics are included in animal feed at subtherapeutic levels for growth promotion and disease prevention. However, recent links between in-feed antibiotics and a rise in antibiotic-resistant pathogens have led to a ban of all antibiotics in livestock production by the European Union in January 2006 and a removal of medically important antibiotics in animal feeds in the United States in January 2017. An urgent need arises for antibiotic alternatives capable of maintaining animal health and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 149 publications
(231 reference statements)
0
65
0
1
Order By: Relevance
“…Histological analysis showed that duodenum villus height was significantly greater in rEP animals than that in the control group (S3a- S3d Fig). Moreover, growth enhancement has been observed in other reports [37,38]. For example, feeding mice with PR39 peptide (4.7 kDa proline-rich AMP)-expressing Lactobacillus casei caused jejunum and duodenum villus height in the intestinal villi to increase [39].…”
Section: Plos Onementioning
confidence: 58%
“…Histological analysis showed that duodenum villus height was significantly greater in rEP animals than that in the control group (S3a- S3d Fig). Moreover, growth enhancement has been observed in other reports [37,38]. For example, feeding mice with PR39 peptide (4.7 kDa proline-rich AMP)-expressing Lactobacillus casei caused jejunum and duodenum villus height in the intestinal villi to increase [39].…”
Section: Plos Onementioning
confidence: 58%
“…Antimicrobial peptides, also known as host defense peptides, have been considered as potential alternatives to antibiotics in livestock and poultry (133135). Antimicrobial peptides are polypeptides, naturally produced by different organisms from prokaryotes to mammals.…”
Section: Nutritional Intervention On Intestinal Development and Healtmentioning
confidence: 99%
“…There are two ways to incorporate the benefits of antimicrobial peptides into animal health and nutrition. One is direct supplementation of exogenous antimicrobial peptides to animal feed, while the other one is to use dietary supplements/ingredients to stimulate the secretion of endogenous antimicrobial peptides by the host (135). Although exogenous or recombinant antimicrobial peptides have shown a great potential to be used as alternatives to replace antibiotics, the effectiveness of those candidates should be carefully verified because the majority of exogenous antimicrobial peptides would be digested in the upper gastrointestinal tract without reaching to the lower part where most pathogens reside.…”
Section: Nutritional Intervention On Intestinal Development and Healtmentioning
confidence: 99%
See 1 more Smart Citation
“…On the account of the cost and stability for the direct administration of HDPs, indirect instigation of synthesis of endogenous HDPs by dietary compounds seems to be a convenient and cost-effective strategy in animal production ( Deng et al., 2018 , Lyu et al., 2018 ). Because these HDP-inducing compounds have no direct interactions with pathogens, they can boost the synthesis of HDPs without triggering resistance and provoking inflammation ( Zhang and Sunkara, 2014 , Robinson et al., 2018 ). The discovery of the 2 cathelicidin genes in the present study will help explore novel antimicrobial strategy in the future.…”
Section: Discussionmentioning
confidence: 99%